Are the determinants of banks' and insurers' capital structures homogeneous? Evidence using South African data - Athenia Bongani Sibindi; Daniel Makina (Cogent Economics & Finance, 2018)
This paper investigates the factors that determine capital structures of financial firms using two separate samples of banks and insurance companies and draws comparisons therefrom. It utilizes two samples of 16 South African banks and 26 South African insurance companies for the period 2006-2015. The relationship between leverage and firm-level determinants of capital structure is tested for each sample. The results show that the standard firm-level determinants of capital structure empirically observed on non-financial firms also apply for banks and insurers. Confirming the fundamental differences between banks and insurance companies, the study observed that the 2007-2009 global financial crisis (GFC) have a negative impact on capital structures of banks (meaning that they deleverage during crises). In contrast, the GFC was found to have a positive impact on capital structures of insurance companies (meaning, unlike banks, they leverage during crises). We find that banks and insurers have target capital structures. Banks adjust to this target at an adjustment speed of 44%, whereas insurers adjust at a lower rate of 21%. In conclusion, the paper finds both commonalities and fundamental differences between the capital structures of banks and insurers.
Keywords: 330; Banks; insurers; capital structure; firm level; regulation; South Africa